Effect of hydroalcoholic extract of ginger on the liver of epileptic female rats treated with lamotrigine - Ameneh Poorrostami; Farah Farokhi Farokhi; Reza Heidari (Avicenna Journal of Phytomedicine, 2014)
Objective: Lamotrigine is an antiepileptic drug, widely used in the treatment of epilepsy; long-term use of this drug can cause hepatotoxicity. Zingiber officinale Roscoe (ginger) possesses antioxidant properties. In present research, the effect ofhydroalcoholic extract of ginger (HEG) on the liver of lamotrigine-treated epileptic rats was investigated Material and Methods: Forty-eight female Wistar rats were selected and allocated to 8 groups of 6 each.  Group 1: Negative controls were treated with normal saline. Group 2: Positive controls were treated with lamotrigine (LTG) (10 mg/kg) daily by gavages for 4 consecutive weeks. Epilepsy was induced in treatment groups by i.p. injection of pentylenetetrazol (PTZ) (40 mg/kg). Group 3: Epileptic group received normal saline (10 ml/kg). Group 4: Epileptic group was treated with LTG (10 mg/kg). Groups 5 and 6: Epileptic groups received HEG (50 and 100 mg/kg). Groups 7 and 8: Epileptic groups received LTG and HEG (50 and 100 mg/kg). At the end of 28 days, blood samples were drawn and their livers were processed for light microscopy. Results: The mean values of TG, CHOL, AST, and ALT activity significantly rose (p